Profiles of local growth and industrial change: Facts and an explanation - Wolfgang Dauth; Jens Südekum (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2012)
In this paper we take a detailed look at the sectoral anatomy of regional growth in German regions over the period 1978-2008. In the aggregate, the German economy is characterized by a secular decline of the manufacturing sector and a rise of the modern service economy. This trend of structural change (Petty's law) by no means occurs uniformly across space, however. Some regions exhibit this trend even at an accelerated pace, while other regions develop their local economic structures against the trend and expand their manufacturing bases. We first develop a novel empirical approach that allows us to categorize all German regions into one out of three groups with pro-trend, anti-trend or featureless regional growth. Afterwards we show that the differential exposure to international trade is an important cause of the divergent patterns of local industrial change. – – Wir untersuchen die sektorale Dimension des regionalen Wachstums über die Jahre 1978-2008. Die deutsche Wirtschaft als Ganzes wurde in diesem Zeitraum geprägt durch den Rückgang der Beschäftigung im verarbeitenden Gewerbe und des gleichzeitigen Wachstums des modernen Dienstleistungssektors. Dieser Trend des Strukturwandels (auch als Petty's law bekannt) wirkt sich jedoch nicht gleichmäßig über das gesamte Bundesgebiet aus. Einige Regionen vollziehen diesen Strukturwandel deutlich schneller während sich andere Regionen entgegen dem nationalen Trend entwickeln. Wir stellen zunächst einen neuen empirischen Ansatz vor, mit dem wir alle deutschen Regionen in eine von drei Gruppen einteilen, welche jeweils durch Pro-Trend, Anti-Trend oder unscheinbares Wachstum gekennzeichnet sind. Danach zeigen wir, dass sich die Unterschiede im regionalen Strukturwandel durch die regionale Betroffenheit vom Welthandel erklären lassen.
Keywords: R11; F16; 330; Structural change; local industry compositions; trade exposure; local employment growth; Regionaler Strukturwandel; Regionales Wachstum; Drei-Sektoren-Hypothese; Regionaler Außenhandel; Deutschland